2017
DOI: 10.1177/0146167217736049
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Dimensions of Childhood Abuse and Neglect Prospectively Predict Poorer Adult Romantic Functioning

Abstract: The present study used data from the Minnesota Longitudinal Study of Risk and Adaptation (MLSRA) to investigate how multiple dimensions of childhood abuse and neglect predict romantic relationship functioning in adulthood. Several dimensions of abuse and neglect (any experience, type, chronicity, co-occurrence, and perpetrator) were rated prospectively from birth through age 17.5 years. Multimethod assessments of relational competence and violence in romantic relationships were conducted repeatedly from ages 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 55 publications
3
41
0
Order By: Relevance
“…A second line of research has explored functioning within adult romantic relationships. Drawing upon a subsample of participants from the MLSRA (N = 179), and using semi-structured interviews and videotaped interactions between study participants and their partners, Labella and colleagues found that childhood abuse and neglect predicted poorer romantic competence (Labella et al 2018). Kapeleris and Paivio (2011) also investigated romantic competence in a sample of 187 undergraduates.…”
Section: Evidence Of Maladaptive Social Functioning Following Childhomentioning
confidence: 99%
“…A second line of research has explored functioning within adult romantic relationships. Drawing upon a subsample of participants from the MLSRA (N = 179), and using semi-structured interviews and videotaped interactions between study participants and their partners, Labella and colleagues found that childhood abuse and neglect predicted poorer romantic competence (Labella et al 2018). Kapeleris and Paivio (2011) also investigated romantic competence in a sample of 187 undergraduates.…”
Section: Evidence Of Maladaptive Social Functioning Following Childhomentioning
confidence: 99%
“…Child abuse and neglect are all-too-common phenomena, with an estimated 12.5% to 40% of American children experiencing these types of adverse caregiving by late adolescence (Finkelhor, Turner, Shattuck, & Hamby, 2013; Hussey, Chang, & Kotch, 2006; Wildeman et al, 2014). Abuse and neglect are associated with poorer social functioning across the life span, including problematic peer relationships and disrupted romantic relationship functioning (Cicchetti & Toth, 2015; Labella et al, 2018; Raby et al, 2018; Widom, Czaja, & Dutton, 2014). Theory and research suggest that the interpersonal consequences of childhood abuse and neglect may extend into the domain of parenting, a key social developmental task of middle adulthood (e.g., Egeland, Jacobvitz, & Sroufe, 1988).…”
mentioning
confidence: 99%
“…Adults with a childhood history of adversity report higher levels of unemployment and lower levels of educational attainment as well as lower overall life satisfaction and wellbeing [10][11][12]. Additionally, adverse experiences in childhood are associated with problems in romantic relationship functioning [13][14][15] and parenting behavior [16,17], contributing to patterns of intergenerational continuity in family adversity [18,19].…”
Section: Introductionmentioning
confidence: 99%